2017
DOI: 10.1042/cs20160669
|View full text |Cite
|
Sign up to set email alerts
|

SerpinC1/Antithrombin III in kidney-related diseases

Abstract: The gene SerpinC1 encodes a serine protease inhibitor named antithrombin III (ATIII). This protease demonstrates both anticoagulant and anti-inflammatory action. ATIII is the most important coagulation factor inhibitor, and even minor changes in ATIII can significantly alter the risk of thromboembolism. ATIII can also suppress inflammation via a coagulation-dependent or -independent effect. Moreover, apart from ATIII deficiency, ATIII and its gene SerpinC1 may also be related to many diseases (e.g. hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 72 publications
2
49
0
Order By: Relevance
“…15 In fact, it is accounted the most inhibitory effector on coagulation. 16 On the other hand, F5 (coagulation factor V) was responsible for the clotting process and it was shown that it had high expressions after one week of treatments with RT in the present study. This process was required to be activated for the healing of damaged tissues caused by RT.…”
Section: Discussionsupporting
confidence: 48%
“…15 In fact, it is accounted the most inhibitory effector on coagulation. 16 On the other hand, F5 (coagulation factor V) was responsible for the clotting process and it was shown that it had high expressions after one week of treatments with RT in the present study. This process was required to be activated for the healing of damaged tissues caused by RT.…”
Section: Discussionsupporting
confidence: 48%
“…One upregulated component of the coagulation and complement pathways was AT III. AT III, encoded by SerpinC1, is an important anti-coagulation molecule and serine protease inhibitor in the coagulation cascade [25,26]. Moreover, there is evidence demonstrating that AT III exerts anti-inflammatory effects, at least partially, by increasing the level of PGI 2, suppressing NF-κB, decreasing leucocyte-endothelial interactions, and inhibiting microvascular leakage [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Increased alpha‐2‐antiplasmin may help to mitigate plasmin destruction of the DEJ and activation of MMPs . The increased levels of antithrombin III may be to balance the (pro)thrombin activity . TIMP‐3 has the broadest MMP inhibition of all TIMPs and may mitigate excessive MMP proteolysis in the pore walls of conspicuous pores similarly increased levels of TFPI and ITIH2 may control other proteases .…”
Section: Discussionmentioning
confidence: 99%